Neighborhood Factors and Language Outcomes of First Nations Preschoolers Living Off Reserve: Findings from the Aboriginal Children's Survey - Findlay, Leanne C.; Kohen, Dafna E. (International Indigenous Policy Journal, 2012)
Language skills in the preschool period are an important indicator of early development and school readiness for children. However, little is known about the association between aspects of the neighborhood and language outcomes for First Nations children. The purpose of the current study was to examine the effects of neighborhood structural and organization features, as well as the mediation of these effects, on the language outcomes of First Nations children aged 2-5 living off reserve. Data from the Aboriginal Children’s Survey was examined. Both neighborhood structure and neighborhood organization were important for language outcomes. In addition, mediation effects were shown, suggesting that family-level as well as neighborhood structural variables are particularly important for the language outcomes of young First Nation children living off reserve.